Intensify agriculture and protect the environment - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Over the centuries, farmers in the tropics have survived through good and bad years, in balance with the environment. But today population pressure on the land precludes practices that enable the environment to recover from extensive cropping...